(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This empirical study investigates the contemporary challenges and pedagogical opportunities in English Language Teaching (ELT) within rural educational settings of Assam, India. Through a mixed-methods approach involving surveys of 156 teachers and 420 students across 45 rural schools in five districts, this research identifies critical infrastructural, pedagogical, and socio-cultural barriers affecting English language acquisition. The findings reveal significant disparities in teacher training (68% untrained in ELT methodologies), resource availability, and student exposure to English outside classroom environments. The study proposes contextually appropriate pedagogical interventions including technology-integrated learning, community-based language programs, and adaptive teaching methodologies. Data analysis demonstrates that multilingual teaching approaches and localized content development can enhance learning outcomes by approximately 34%. This research contributes to the discourse on equitable language education in marginalized geographical contexts and offers evidence-based recommendations for policy formulation and implementation.